PREPARATION AND CHARACTERIZATION OF SOME SILICON (IV) COMPLEXES (Sciences & Technology. A, exactes sciences, 2008)
Silicon(IV) complexes containing mixed ligands: Shiff-bases (AH) {derived from 2- or 3- amino-pyridine with 2-hydroxy- or 3-me- thoxy- or 2-hydroxy-3-methoxy-benzaldehyde} and benzalde- hyde semicarbazone (BSCH), have been prepared. The resulted complexes have been characterized by elemental analysis, molar conductance values, infrared and electronic spectral data. Complexes of the type [Si(BSCH)2(AH)]Cl4, [Si(BSC)2(AnH)]Cl2 and [Si(BSC)2(A)]Cl (where n=2 or 3, A=deprotonated Schiff-base ligands , BSC= deprotonated semicarbazone) have been proposed in neutral and basic medium, respectively.